Предмет: Математика,
автор: Vishnya18
Алгебра 9 класс , помогите пожалуйста
Приложения:
Ответы
Автор ответа:
0
(x-2)^4+3(x-2)^2-10=0
(x-2)^2 заменим у, т.е. (x-2)^2=y
y^2+3*y -10=0
D=b^2-4ac=9+120=129
y1=-3+корень из 129 / 2
y2=-3-корень из 129 / 2
(x-2)^2 заменим у, т.е. (x-2)^2=y
y^2+3*y -10=0
D=b^2-4ac=9+120=129
y1=-3+корень из 129 / 2
y2=-3-корень из 129 / 2
Автор ответа:
0
спасибо большое)
Автор ответа:
0
не за что!:)
Похожие вопросы
Предмет: Математика,
автор: tunec666
Предмет: История,
автор: akbarmuk08
Предмет: Математика,
автор: ajsamutalina
Предмет: Алгебра,
автор: Ilona41
Предмет: Алгебра,
автор: Изабелка